Molecular Docking Screening and Pharmacokinetic Studies of Some Boron-Pleuromutilin Analogues against Possible Targets of Wolbachia pipientis - Fabian Audu Ugbe; Gideon Adamu Shallangwa; Adamu Uzairu; Ibrahim Abdulkadir (Institute for Research and Community Services Universitas Muhammadiyah Palangkaraya, 2022)
Lymphatic filariasis and onchocerciasis are two common filarial diseases caused by a group of parasitic nematodes called filarial worms, which co-habit with the bacteria organism Wolbachia. One good treatment approach seeks Wolbachia as a drug target. Here, a computer-aided molecular docking screening was conducted on a series of 52 pleuromutilin analogs against four Wolbachia enzymes: α-DsbA1 (PDB: 3F4R), α-DsbA2 (6EEZ), OTU deubiquitinase (6W9O), and cytoplasmic incompatibility factor CidA (7ESX) to find a more potent drug candidate(s) for the treatment of filarial diseases. The docking investigation was performed using the iGEMDOCK tool, while NAMD was utilized for the Molecular Dynamic (MD) simulation. The results of the virtual screening identified four ligand-protein interaction pairs with the highest binding affinities in the order: 17_6W9O (-117.31 kcal/mol) > 28_6EEZ (-104.43 kcal/mol) > 17_7ESX (-102.56 kcal/mol) > 41_7ESX (-101.51 kcal/mol), greater than that of the reference drug doxycycline_7ESX (-92.15 kcal/mol). These molecules (17, 28, and 41) showed excellent binding interactions, making very close contact with the receptors’ amino acid residues. They also showed better pharmacokinetic properties than doxycycline because they showed high intestinal absorption, were orally bioavailable and showed no AMES toxicity. Also, the stability of 17_6W9O interactions was confirmed by the MD simulation. Therefore, the selected molecules could be developed as potential drug candidates for treating filarial diseases.